O papel dos agentes colonizadores em Cidade Gaúcha-PR a partir da década de 1950 : um estudo na perspectiva neo-institucionalista - Gomes, Valdir (2014)
This study is based on the theoretical principles of sociological institutionalism, guided by the concepts of environmental rationality and economic rationality, and the prospect of a multidisciplinary approach. The aim is to characterize the role of pioneer settlers during the process of occupation of territorial area once belonging to the municipality of Rondon-PR, currently the municipality of Cidade Gaúcha, in the Northwestern Paraná, from de 1950s. The research seeks to identify the action of settlers concerning areas of permanent forest preservation, riparian forests and water resources, and examine whether the process was in accordance with legal procedures prevailing at that time. Concerning its form, this study is classified as exploratory, and its nature is descriptive. As for methodological procedures, it was conducted through field research, following a systemic approach in theoretical perspective. Results showed that 82% of settlers had no tradition and knowledge in coffee production, front agricultural focus at that time. Also, most of them were unaware of 1934 Forest Code, prevailing at that time. Moreover, respondents indicated the complete absence of Government and of the agency of colonization for guiding, monitoring and enforcing laws, rules and norms in the occupation process. Thus, one can understand the role of pioneer settlers in the region, by removing forests and changing the area into agricultural fields. Data showed low professionalization of settlers and inefficiency of regulatory agents (Government and agency of colonization) concerning prevailing legal requirements. To sum up, it was concluded that decisions and actions of pioneer settlers were based on mimetic isomorphism, lending support to the hypothesis of this study. In this sense, the regional occupation of Cidade Gaúcha ?PR by those geographic agents were aligned to primary guidance from previous occupation of pioneer fronts in Norte Pioneiro and Norte Novo, through the experience of workers from those regions and the first settlers in the studied region, which started the process and eventually became the model for subsequent settlers.